Liming, micronutrient application, and rice and dry-bean production in a lowland soil - Flávio Dynia, José; Francisco Valente Moraes, José (Pesquisa Agropecuaria Brasileira, 1998)
Grain production, and absorption of nutrients by flooded rice (cv. Cica-8, and BR IRGA-409) and dry-bean (cv. Carioca, and LM 30030) planted in successive and alternate crops in a Low Humic Gley soil of the county of Goianira, GO, Brazil, were evaluated as affected by treatments which associated five lime doses and two micronutrients doses. Lime did not influence the grain yield of rice or bean, and micronutrients increased significantly (p < 0.05) the yield of beans, but not of rice. In the plots which had received no micronutrients, the bean plants showed symptoms of B deficiency and Mn toxicity. In all treatments, the rice cv. BR IRGA-409 absorbed more Fe than cv. Cica-8, but none of the two cultivars showed any symptom of Fe toxicity.
Keywords: FTE; nutritional deficiency; boron; zinc; manganese; iron; waterlogging